GROWTH RESPONSE AND PRODUCTION OF TWO VARIETIES OF OKRA (Abelmoschus esculantus L. Moench) ON GIVING VARIOUS TYPES OF ORGANIC FERTILIZER - Ria Anindi Antika Barus (Institute of Computer Science (IOCS), 2021)
Okra is a vegetable plant that can be consumed directly or made into processed foods and has good pharmacological effects in the health sector. Okra has a high economic value when compared to other vegetables. The problem faced in okra cultivation is that this plant is not well known by the Indonesian people. The application of organic fertilizer to okra cultivation is expected to improve quality and quantity. This research was carried out on community land for the construction of the Medan Selayang sub-district with an altitude of ± 25 meters above sea level. This research was conducted from May to September 2016, using a randomized block design with 2 treatment factors. The first factor is varieties with 2 types, namely burgundy red okra and Garibar green okra and the second factor is the application of organic fertilizer with 4 types, namely without organic fertilizer, compost, vermicompost fertilizer, and chicken manure. The results showed that the varietal treatments were significantly different on plant height 10-14 WAP, flowering age, number of fruit per plant, fruit weight per plant, number of fruit per plot, fruit length, fruit diameter and canopy wet weight. The application of various kinds of organic fertilizers significantly affected the parameters of plant height increase 10-14 WAP, number of leaves 10-14 WAP, flowering age, number of fruit per plant, fruit weight per plant, and number of fruit per plot. The interaction between varietal treatment and the application of various kinds of organic fertilizers had a significant effect on the increase in plant height 10-14 WAP.